Luting Cement for Implant Retained Prosthesis - Ajay Gaikwad (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:There are only two ways to connect an implant prosthesis to the implant i.e. SR and CR implant-supported restorations. The most important factor to consider when making the right choice for luting cements for implant-retained prostheses is how cement's chemical properties affect the surface texture of titanium abutments and Co-Cr alloys. Aim: To assess the best long term luting cement for IRP based on bond strength & surface integrity. Material & Method: A total of 60 samples were included with luting cements i.e. GIC, ZnPO4 and non- eugenol ZnO were evaluated on 2 sub-groups of A & B i.e. I, II,III in Thermocycling and autoclave respectively. Result: We have found significant difference for surface roughness on evlaution of group A &B III as the p value was 0.001 while non significant on comparison of group A &B for I & II as the p value was 0.481 and 0.370 respectively. Conclusion: In order to improve the long-term retention and surface integrity of titanium alloy prostheses, both luting cement and GIC prostheses may be utilized as surface cement.